Assessment of the physicochemical and sensory characteristics of fermented camel milk fortified with Cordia myxa and its biological effects against oxidative stress and hyperlipidemia in rats - Atwaa, El Sayed Hassan; Shahein, Magdy Ramadan; Raya-Álvarez, Enrique; Abd El-Sattar, El Sayed; Hassan, Moustafa A. A.; Hashim, Madeha Ahmed; Dahran, Naief; El-Khadragy, Manal F.; Agil, Ahmad; Elmahallawy, Ehab Kotb (Frontiers in Nutrition, 2023)
Natural feed additives and their potential benefits in production of safe and highly nutritious food have gained the attention of many researchers the last decades. Cordia myxa is a nutrient-dense food with various health benefits. Despite this fact, very limited studied investigated the physicochemical and sensory impacts of incorporation of fermented camel milk with Cordia myxa and its biological effects. The current study aimed to assess the physical, chemical, and sensory characteristics of fermented camel milk (FCM) fortified with 5, 10, and 15% Cordia myxa pulp. The study demonstrated that fortification of camel milk efficiently enhanced protein, total solids, ash, fibre, phenolic substance, and antioxidant activity. When compared to other treatments, FCM supplemented with 10% Cordia myxa pulp had the best sensory features. In addition, FCM fortified with 10 % Cordia myxa pulp was investigated as a potential inhibitor of hypercholesterolemia agents in obese rats. Thirty-two male Wistar rats were split into two main groups including normal pellet group (n= 8) served as negative control group (G1) and a group of hyperlipidemic animals (n=24) were feed on a high-fat diet (HFD). Hyperlipidemic rats group (n=24) were then divided into three subgroups (8 per each); second group or positive control (G2) which include hyperlipidemic rats received distilled water (1 mL/day), the third group (G3) involved hyperlipidemic rats feed on FCM (10 g/day) and the fourth group (G4) included hyperlipidemic animals feed on 10g/day FCM fortified with 10% of Cordia myxa pulp by oral treatment via an intestinal tube for another four weeks. In contrast to the positive control group, G 4 treated with Cordia myxa showed a substantial decrease in malondialdehyde, LDL, cholesterol, triglycerides, AST, ALT, creatinine, and urea levels, while a significant increase in HDL, albumin, and total protein concentrations. The number of large adipocytes decreased while the number of small adipocytes increased after consumption of fortified FCM. The results indicated that fermented milk fortified with Cordia myxa pulp improved the functions of the liver and kidney in hyperlipidemic rats. These results demonstrated the protective effects of camel milk and Cordia myxa pulp against hyperlipidemia in rats.